Financiamento da urbanização capitalista: a obra de “Requalificação” da Avenida Beira-mar em Fortaleza-CE - Moreira, Antônio Victor de Mendonça (2023)
The capitalist expansion in the metropolis Fortaleza gives rise to profound changes in its own socio-spatial dynamics, processes that redefine the production of the seafront of the eastern sector, thus specializing in tourist activities and sumptuary merchandise trade. From this, in this sector of the metropolis, built spaces for collective use assume a leading role in the inherent contradictions of urban practices based on the self-valorization of value. In fact, urbanization engenders intricate processes that involve planning, financing, execution, coordination and control of built spaces for collective use, which function as components of fixed capital. In this context, the present dissertation takes as an empirical basis the process of the urban financing of “requalification” of Avenida Beira-mar, through contracting by the Municipality of Fortaleza of loan in foreign currency, in the year of 2018, with a multilateral development bank. With the effect of outlining a sociological analysis of the object in question, we seek to establish mediations, from different levels of abstraction and scales of analysis. For that, three specific movements were carried out in the constitution of the investigation method: the first consists of a review of the founding categorical basis for the research; the second refers to the construction of theoretical-analytical mediations, necessary to connect the chosen categorical base and new levels of concretion of the socio-spatial reality; the third is based on the identification of the main agents, institutional organs and financial flows involved in the financing of the “requalification” of build space of Avenida Beira-mar. Thus, these specific methodological movements make it possible to verify the centrality of the functions performed by the State in the conformation of nexuses between urbanization and the forms of production, circulation and realization of socially produced wealth, under the aegis of the interest-bearing capital. This is concretely manifested with the increase in the level of indebtedness in foreign currency of the Municipality of Fortaleza, between 2017 and 2021, with the aim of financing works to improve the built spaces for collective use, including Avenida Beira-mar and its immediate surroundings.